2008
DOI: 10.1016/j.jcv.2007.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hepatitis C viremia in a large cohort of HIV-infected and -uninfected women

Abstract: Background-Coinfection with hepatitis C virus (HCV) is common among HIV-infected women.Objective-To further our understanding of the risk factors for HCV viremia and the predictors of HCV viral load among women.Study design-We investigated sociodemographic, immunologic, and virologic factors associated with presence and level of HCV viremia among 882 HIV-infected and 167 HIVuninfected HCV-seropositive women at entry into the Women's Interagency HIV Study.Results-Plasma HCV RNA was detected in 852 (81%) of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
(59 reference statements)
3
25
0
Order By: Relevance
“…Prior work has demonstrated the potential for both drug-related and sexual HCV transmission. Shared non-injection drug use paraphernalia (e.g., mouthpieces, straws) 29 and the use of inhaled and smoked stimulants (e.g., crack, cocaine) have been associated with elevated HCV prevalence among substance-using and low-income women 27 , women at risk of or living with HIV in the U.S. 30 , and men and women who use drugs 31 . Additionally, previous work has shown that elevated sexual and drug-related risks are often experienced within the context of overlapping risks related to sex work and crack use 9,32 ; for example, associations have been reported between HCV infection and non-injection (i.e., inhaled, smoked) crack use, as well as sex work while using crack 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has demonstrated the potential for both drug-related and sexual HCV transmission. Shared non-injection drug use paraphernalia (e.g., mouthpieces, straws) 29 and the use of inhaled and smoked stimulants (e.g., crack, cocaine) have been associated with elevated HCV prevalence among substance-using and low-income women 27 , women at risk of or living with HIV in the U.S. 30 , and men and women who use drugs 31 . Additionally, previous work has shown that elevated sexual and drug-related risks are often experienced within the context of overlapping risks related to sex work and crack use 9,32 ; for example, associations have been reported between HCV infection and non-injection (i.e., inhaled, smoked) crack use, as well as sex work while using crack 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Other coinfections such as hepatitis C virus (HCV) infection are also more prevalent substance users and this may accelerate HIV disease progression. Interestingly, one recent cross-sectional investigation with the WIHS observed that a history of crack-cocaine use and cigarette smoking were independently associated with elevated HCV viral load among HIV-positive women (Operskalski et al, 2008). Finally, increased rates of sexual risk taking among stimulant users may lead to the acquisition of co-morbid sexually transmitted infections like syphilis that can promote HIV progression if left untreated (Wong et al, 2005).…”
Section: Confounding Factors In Studies Examining the Effect Of Stimumentioning
confidence: 99%
“…In addition to issues related to mental health and drug treatment, stimulant use has been consistently linked with a variety of serious physical health consequences, including HIV and hepatitis C infections (Fischer et al, 2008; Ivy et al, 2013; Novak et al, 2013; Nyamathi et al, 2002), poor clinical outcomes among HIV and HCV-infected women (Carrico et al, 2011; Operskalski et al, 2008; Riley et al, 2011), arrhythmias and sudden death caused by stimulant-induced arrhythmia occurring in the absence of traditional risk factors like infarction (Hsue et al, 2007; Lange and Hillis, 2001). We recently reported a 3% annual mortality rate among 300 homeless women living in San Francisco over a four-year observation period (Riley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%